The eyes of texas eaudiobook Matt jensen series, book 8. - Johnstone, William W. (Matt Jensen: The Last Mountain Man, 2017)
A true legend in the Western genre, William W. Johnstone captivated audiences with his epic Last Mountain Man series. Best-selling author J.A. Johnstone continues this tradition in The Eyes of Texas, which finds Matt Jensen in the deadly Texas town of Shady Rest. After Jensen guns down a ruthless killer in self-defense, he's suddenly in line for a $5,000 bounty. Trouble is, the dead man's kin aren't too keen on Matt staying alive to collect.